Literature Study on Analysis of Risky Riding Behavior in Motorcycle Riders - Sembiring, Salsabila; Panjaitan, Nismah; Ginting, Rosnani (Jurnal Sistem Teknik Industri, 2026)
Risky driving behavior among motorcyclists is one of the main factors contributing to the high traffic accident rates, especially in developing countries. This study aims to identify, analyze, and synthesize various factors influencing risky riding behavior among motorcyclists thru a Systematic Literature Review (SLR) approach. The research method was conducted by searching for scientific articles from various academic databases, such as Google Scholar, Scopus, and ScienceDirect, using keywords related to risky driving behavior, road safety, and motorcycle riders. The literature selection process was conducted based on inclusion and exclusion criteria to obtain relevant and high-quality articles. The study results show that risky driving behavior is influenced by several main factors, namely individual factors, psychological factors, environmental factors, and social and regulatory factors. The most frequently observed forms of risky behavior include speeding, using mobile phones while driving, not using personal protective equipment, running red lights, and aggressive behavior on the road. This study concludes that efforts to reduce risky driving behavior require a multidimensional approach thru safety education, consistent law enforcement, and the development of transportation policies focused on the safety of road users. This research is expected to serve as a foundation for the development of driving safety strategies and a reference for future studies.